La religión y el origen de la cultura occidental - Dawson, Christopher, 1889-1970 (Ensayos (Ediciones Encuentro), 2010)
An essential work of European history, this classic study sweeps from the fall of Rome to the dawn of the Renaissance as it shows how Christianity, its leaders, and its institutions changed the face of Western culture.